KINERJA PEGAWAI PADA KELURAHAN TONDO KOTA PALU - Kamaluddin, Kamaluddin (Katalogis, 2018)
This study aims to determine the performance of employees in the Tondo district office in Palu. This study was designed qualitatively. The informants are Secretary Lurah, Section Head of Government, staff / pegwai and community Tondo Village residents were determined using purposive data collection method consists of observation, interviews and documentation. The technical analysis of the data, including data collection, data reduction, data presentation, and conclusion. The results of the study showed that, Employee Performance Employees at the Village Office Tondo seen from five aspects: (1) Quality of Work, (Quality of work) performance of employees / staff has been good, although not optimal, because, as finishing work, file handling troubled and delay, it is in because the working hours of staff / employees are not in accordance with the existing provisions in the office in general, this is what causes the Village office Tondo employee performance is not maximized. (2) Timeliness (Pomptnees) of the office hours staff / employee do not correspond, it is their show, sometimes they go in at half past nine and sometimes hours of 9 passes, of things kesuian assigned task is not appropriate for this show in their work often No errors, file problems and no delays. It also researchers felt with what is perceived by the public. (3) Aspects Initiatives, (Initiative) resolving employee response has been good enough job, such as job sipatnya urgent and society want them to be resolved immediately. But sometimes there are still people who do not feel satisfied with the results of the work, as there is still a delay in completing the work. (4) Aspects of Capability (Capability), the dominant educational backgrounds owned pegwai is appropriate, namely in terms of the number of employees 12 7 between berijzah strata one, 1 Megister and the rest of certified high school and junior high. But sometimes there are still people who do not feel satisfied, as there is still problematic file and a delay in serving the community. (5) Aspect Communications (Communication, employer responses in completing his work is good enough, like Every meeting is always held input/opinions of staff / employee to know what their complaints are looking for solutions when there are problems. But sometimes there are still people who do not feel satisfied with the results of the work are often late in working on files such as the delay in completing the work.